Information needs and decision‐making preferences of older women offered a choice between surgery and primary endocrine therapy for early breast cancer. Issue 12 (17th April 2017) - Burton, Maria; Kilner, Karen; Wyld, Lynda; Lifford, Kate Joanna; Gordon, Frances; Allison, Annabel; Reed, Malcolm; Collins, Karen Anna
Abstract: Objectives: To establish older women's ( ≥75 years) information preferences regarding 2 breast cancer treatment options: surgery plus adjuvant endocrine therapy versus primary endocrine therapy. To quantify women's preferences for the mode of information presentation and decision‐making (DM) style. Methods: This was a UK multicentre survey of women, ≥75 years, who had been offered a choice between PET and surgery at diagnosis of breast cancer. A questionnaire was developed including 2 validated scales of decision regret and DM preferences. Results: Questionnaires were sent to 247 women, and 101 were returned (response rate 41%). The median age of participants was 82 (range 75 to 99), with 58 having had surgery and 37 having PET. Practical details about the impact, safety, and efficacy of treatment were of most interest to participants. Of least interest were cosmetic outcomes after surgery. Information provided verbally by doctors and nurses, supported by booklets, was preferred. There was little interest in technology‐based sources of information. There was equal preference for a patient‐ or doctor‐centred DM style and lower preference for a shared DM style. The majority (74%) experienced their preferred DM style. Levels of decision regret were low (15.73, scale 0‐100). Conclusions: Women strongly preferred face to face information. Written formats were also helpful but not computer‐based resources. Information that was found helpful to women in the DM process was identified. The study demonstrates many women achieved their preferred DM style, with a preference for involvement, and expressed low levels of decision regret.